IMPLEMENTASI PENDIDIKAN KARAKTER TERHADAP PERILAKU MORAL SISWA MELALUI PEMBELAJARAN DI LINGKUNGAN SEKOLAH DASAR - Anggun Setiawan; Arri Handayani; Dini Rahmawati (STKIP Subang, 2024)
This article aims to describe the essence of the implementation of character education through learning activieis in school environment. Character education has an important role in the moral cultivating of students relating to moral knowing, moral feeling, and moral behavior. The three aspects must be developed in order to realize students with noble character. In connection with the concept of school management, character education ought to be internalized through learning activities, extracurricular activities, and intracuricular activities. The formation of character through environmental factors can be done through several strategies, including modelling, intervention, habituation that is done consistently and reinforcement. In other words, developments in character formation require exemplary transmission, interventions through learning, training, continuous long- term habituation that is carried out continuously and reinforced, and must be balanced with noble values.